Monitoring articles on the use of nanocomposites with polyurethane matrix applied to tissue engineering for bone repair (Research, Society and Development, 2021)
Nanocomposites with polyurethane matrix are materials with interesting properties for tissue engineering and can be used in the manufacture of scaffolds for bone regeneration. The objective of this research was to evaluate the evolution of scientific publications related to polyurethane matrix nanocomposites applied to bone tissue regeneration. Searches were conducted in the databases of Web of Science and Scopus, using a combination of keywords, and the results were tabulated and analyzed. The first documents date from 2009. China holds the largest number of publications, followed by Malaysia and Vietnam. The main research areas are Engineering, Materials Science and Chemical Engineering. An increasing appreciation of the theme was noticed, with an increase in the production and impact of these publications. It can be considered that the question raised has great relevance because it is a promising field of study that promises to bring important advances to bone tissue engineering.